Acts of Requesting as Realized by English for Specific Purposes Students - Nugroho, Arif; Astuti, Nuning Wahyu; Atmojo, Arief Eko Priyo (State institute of islamic studies salatiga, 2021)
The success of language learners’ intercultural communication highly depends on their acquisition of not only grammatical knowledge but also pragmatic aspects of the target language. However, research examining English for specific purposes (ESP) learners’ request realization, as a crucial indicator of pragmatic competence, still remains a paucity of evidence. Addressing this issue, the present study aims to examine English for specific purposes (ESP) students’ most frequently used request strategy and their reasons behind the selected strategy. To this end, 36 ESP students of a public university in Surakarta Indonesia were involved in a descriptive qualitative study. A set of Discourse Completion Test (DCT), role-play, and semi-structured interview were employed as a means of data collection. The data were analyzed based on Blum-Kulka and Olshtain’s Cross-Cultural Study of Speech Act Realization Patterns (CCSARP) and followed by thematic content analysis for the interview responses. The results depicted that conventionally indirect requests were the most frequently used strategy by the students than other strategies, i.e. direct request, and non-conventionally indirect request. The semi-structured interview further revealed that cultural factors, degree of politeness, and social distance among the interlocutors became the primary reasons for the students’ massive selection of conventionally indirect strategies. These results offer fruitful insights for English language teaching stakeholders as an effort to equip ESP students with satisfactory pragmatic and cross-cultural knowledge.Keywords: acts of requesting, pragmatics, request strategies,